THE INFLUENCE OF PRODUCT QUALITY ON CONSUMER SATISFACTION OF DFC CHICKEN (DEWE FRIED CHICKEN) IN SORONG DISTRICT - Edwar, Rizka Cintya (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
This research aims to determine the effect of product quality on consumer satisfaction with DFC (Dewe Fried Chicken) chicken in Sorong district. This research used quantitative methods with a sample of 100 consumers who had previously consumed DFC chicken. The data collection technique is by distributing and distributing questionnaires and then the data is processed using SPSS. The results of this research show that product quality has a positive and significant effect on consumer satisfaction, so it can be concluded that if product quality increases, consumer satisfaction will increase.